Elevated ZNF703 Protein Expression Is an Independent Unfavorable Prognostic Factor for Survival of the Patients with Head and Neck Squamous Cell Carcinoma. (29th April 2015) - Yang, Hang; Jiang, Wen-Qi; Cao, Ye; Sun, Yong-An; Wei, Jing; An, Xin; Zhang, Ying-Chun; Song, Ming; Wang, Shu-Sen; Yuan, Zhong-Yu; Peng, Rou-Jun; Chen, Tan-Huan; et al.
Abstract : Aim . Data from The Cancer Genome Atlas (TCGA) show that the ZNF703 gene amplifies and overexpresses in head and neck squamous cell carcinomas (HNSCC). However, the clinical relevance of this observation in HNSCC is unclear. The purpose of this study was to clarify the expression of ZNF703 protein and its prognostic effect on HNSCC. Methods . Two hundred ten HNSCC patients from Sun Yat-Sen University Cancer Center with complete survival follow-up were included in this study. Tumor samples from primary sites were collected. The expression of the ZNF703 protein was tested by immunohistochemistry (IHC). Results . The high expression of ZNF703 in HNSCC tumor tissues was significantly higher than that of the matched noncancerous tissues (48.6% versus 11.6%, P < 0.001 ). ZNF703 overexpression was correlated with tumor position (laryngeal carcinoma) and recurrence (allP < 0.05 ). Multivariate analysis revealed that ZNF703 protein overexpression was an independent prognostic factor (P = 0.0 22, hazard ratio = 1.635, 95% CI 1.073–2.493) in HNSCC patients. Conclusion . ZNF703 overexpression is associated with adverse prognosis in HNSCC, which might be a novel biomarker of HNSCC.